Causal associations between disorders of lipoprotein metabolism and ten cardiovascular diseases - Gao, Qiannan; Tan, Jiang-Shan; Fan, Luyun; Wang, Xiaoqi; Hua, Lu; Cai, Jun (Frontiers in Cell and Developmental Biology, 2022)
Disorders of lipoprotein metabolism have been linked with an increased risk of cardiovascular diseases (CVDs) but the causal association is unclear. In this study, we investigated the causal association between disorders of lipoprotein metabolism and CVDs using two-sample Mendelian randomization (MR). The exposure was obtained from Finn genome-wide association studies (14,010 cases, 197,259 controls), and the corresponding CVDs were extracted from the largest published genome-wide association studies. A random-effects inverse-variance weighted method was used for the main analyses with a complementary analysis using the weighted median and MR-Egger approaches. Multiple sensitivity analyses were performed to assess horizontal pleiotropy. The MR analysis indicated positive associations of disorders of lipoprotein metabolism with coronary artery disease (odds ratio [OR] 1.670, 95% confidence interval [CI] 1.373–2.031; P<0.001), aortic aneurysm (OR 1.394, 95% CI 1.199–1.619; P<0.001), heart failure (OR 1.20, 95% CI 1.115–1.294; P<0.001), hypertension (OR 1.011, 95% CI 1.006–1.091; P<0.001), old myocardial infarction (OR 1.004, 95% CI 1.002–1.007; P=0.001), and stroke (OR 1.002, 95% CI 1.001–1.003; P=0.001). There is a suggestive causal relationship between disorders of lipoprotein metabolism and atrial fibrillation (OR 1.047, 95% CI 1.006–1.091; P=0.026) and acute myocardial infarction (OR 1.003, 95% CI 1.001–1.005; P=0.012). There was limited evidence of a causal association between disorders of lipoprotein metabolism and peripheral vascular disease and venous thromboembolism. Our findings indicate a significant causal association between disorders of lipoprotein metabolism and many CVDs, including coronary artery disease, aortic aneurysm, heart failure, hypertension, old myocardial infarction, and stroke. These associations may be useful for development of treatment strategies that regulate lipoprotein metabolism in patients with CVD.